MANAJEMEN MEDIA DIGITAL - Media Sucahya (Tarbawi, 2017)
Communication technology increasingly cement the role of information as a commodity that has high selling value, including information published print media. Technology not only affects the production and distribution of print media, but also pushes toward where the media business leads. Internet and multimedia technologies make the print media an added value and provide a foundation for the development of the media industry. Technology spawned convergence by bringing together old technology in new technology, where old technology adds value to new technologies. Convergence concept must be done by print media. Convergence creates a change in the foundations of people's lives in communicating, especially in the media industry. Tempo Media Group as one of the leading media in Indonesia, successfully transformed from traditional media into digital media. Tempo Media Group successfully mated Tempo magazine, Koran Tempo, Tempo.co, and Tempo digital shop. This study uses a descriptive qualitative approach that describes a problem with depth. Technique of collecting data using library study or documentation with research object of Tempo Media Group. The purpose of this research is to know how the strategy done by Tempo Media Group entering the digital media industry. The results revealed that the steps taken by Tempo Media Group from media organization side converged by forming a newroom together, increasing investment for communication technology, and creating an adaptive work culture to innovation. Keywords: Communication Technology, Convergence, Newsroom Management